PERUBAHAN SIFAT FISIKO-KIMIAWI SELAMA PROSES FERMENTASI BIJI KAKAO SEGAR: (Changes in Physical-Chemical Properties During The Fresh Cocoa Fermentation Process) - Nandi K Sukendar; Abu Bakar Tawali; Salengke Salengke; Adiansyah Syarifuddin; Andi Hasizah Mochtar; Andi Fakhruddin (Hasanuddin University Food Science and Technology Study Program, 2019)
Cocoa is a plantation commodity that requires fermentation to improve the quality of flavor and aroma. Research on changes in physical and chemical properties during the spontaneous fermentation process of fresh cocoa beans for weight scales of 20, 40 and 60 kg have been carried out. This study aims to obtain information as an indicator of the success rate of the fermentation process of fresh cocoa beans, both on a small and large scale. The fermentation process lasts for 6 days with stirring starting on the second day until the sixth day, with an interval of 24 hours. The study design uses a randomized block design method (RBD) with two factors, namely the weight scale of seeds per box and fermentation time with three replications. The data obtained were analyzed qualitatively and quantitatively. Based on the observed parameter indicators, namely temperature, pH and total acid, there was no significant difference in the profile of the physico-chemical properties during the fermentation process between the three weight scale levels. The physico-chemical condition shows a straight relationship with the quality of fermented cocoa beans, in accordance with the results of the cut test.